2013
DOI: 10.1002/aenm.201200673
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Reduced Efficiencies of Organic Solar Cells Employing Fullerene Multiadducts as Acceptors

Abstract: The use of fullerenes with two or more adducts as acceptors has been recently shown to enhance the performance of bulk‐heterojunction solar cells using poly(3‐hexylthiophene) (P3HT) as the donor. The enhancement is caused by a substantial increase in the open‐circuit voltage due to a rise in the fullerene lowest unoccupied molecular orbital (LUMO) level when going from monoadducts to multiadducts. While the increase in the open‐circuit voltage is obtained with many different polymers, most polymers other than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
141
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(148 citation statements)
references
References 72 publications
7
141
0
Order By: Relevance
“…For instance, it is still unclear why specic acceptors work well only in combination with certain donors. 1 Moreover, thorough knowledge has not been established why small variations in the chemical structure of the active materials in certain cases can lead to signicant differences in device performance while in other scenarios essentially identical device characteristics are obtained.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it is still unclear why specic acceptors work well only in combination with certain donors. 1 Moreover, thorough knowledge has not been established why small variations in the chemical structure of the active materials in certain cases can lead to signicant differences in device performance while in other scenarios essentially identical device characteristics are obtained.…”
mentioning
confidence: 99%
“…One reason for these differences that are observed in devices even for structurally very similar materials is that the manipulation of the chemical structure oen results in alteration of the energy levels, 1,3 which, in the case of the LUMO of the acceptor, should either promote charge dissociation or increase the open circuit voltage (V oc ) with a given donor. Chemical changes lead, however, also to a different miscibility of the two components, which can affect OPV device characteristics considerably, 4 as well as a different thermal behaviour.…”
mentioning
confidence: 99%
“…Although many C 60 derivatives and a new C 84 derivative have been synthesized and utilized as acceptors in OPVs, only handful C 60 derivatives achieved good solubility in organic solvents, desired electron mobility to have good charge transport, broad absorption to contribute to the photocurrent and suitable electronic levels to have efficient charge dissociation. 19,20 The research effort devoted to new fullerene acceptor materials are increasing but the new fullerene derivative acceptors showing better photovoltaic performances than PCBM are very few. PCBM is still the most important acceptor material used in the organic solar cell studies.…”
Section: -15mentioning
confidence: 99%
“…Nevertheless, a limiting factor to this polymer: C 60 bisadducts strategy was evidenced for some blends where a simultaneous dramatic loss in the J sc and lower electron mobilities resulted in a reduced PCE for most polymers other than P3HT [79]. It was identified that the principal 40401-p7 reason was the correlation between J sc and the free energy of the photoinduced charge generation ΔG CT .…”
Section: -P5 Epj Photovoltaicsmentioning
confidence: 99%